2011
DOI: 10.1111/j.1447-0756.2010.01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sublingual misoprostol versus intravenous oxytocin on reducing blood loss at cesarean section in Nigeria: A randomized controlled trial

Abstract: Sublingual misoprostol was as effective as i.v. oxytocin infusion in reducing blood loss at cesarean section. It offers several advantages over oxytocin, including long shelf life, stability at room temperature, and oral administration, which make it a suitable uterotonic agent in low-resource areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
8
43
0
Order By: Relevance
“…These findings are consistent with some other researches [7,23]. Some mentioned oxytocinmediated hemodynamic changes in cesarean are decreasing blood pressure and peripheral vascular resistance plus increasing heart rate [26,27].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are consistent with some other researches [7,23]. Some mentioned oxytocinmediated hemodynamic changes in cesarean are decreasing blood pressure and peripheral vascular resistance plus increasing heart rate [26,27].…”
Section: Discussionsupporting
confidence: 82%
“…The sublingual route allows fast absorption of drug and more sustained therapeutic effect than oral administration as it avoids first-pass effect. Misoprostol stimulates uterine contractions by selectively binding to myometrial prostanoid receptors, and it has a long half life and minimal adverse effects, such as gastrointestinal symptoms, shivering, pyrexia, fatigue, and headache [7]. It is reported that sublingual misoprostol (800 lg) is a safe and effective treatment for women experiencing PPH [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Misoprostol has been evaluated as an alternative to oxytocin during cesarean delivery, and has also been used in combination with oxytocin. [7][8][9][10][11][12][13][14][15][16][17] Two meta-analyses concluded that misoprostol was as effective as oxytocin and that the combination of the misoprostol and oxytocin is better than is oxytocin alone for the prevention of PPH. However, women with known risk factors for PPH, who are expected to benefit from an additional oxytocic agent, were excluded from some of the studies.…”
mentioning
confidence: 99%
“…The list of studies excluded is available from the authors upon request. Seventeen studies, 38-54 including 3174 women, fulfilled inclusion criteria of which seven evaluated misoprostol versus oxytocin (n=700), 39,40,42,45,47,49,54 one evaluated misoprostol versus ergometrine (n=374), 51 eight evaluated misoprostol plus oxytocin versus oxytocin (n=1918), 41,43,44,46,48,50,52,53 and one 3-arm trial evaluated misoprostol versus oxytocin versus misoprostol plus oxytocin (n=182). 38 …”
Section: Resultsmentioning
confidence: 99%